Applying English Songs To Children In Second Language Acquisition - Gina Regiani; Pitri Nuraeni; Lusiana Suciati Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research explores the use of English songs as an aid in second language acquisition (SLA) among children. Utilizing a qualitative method with a case study approach, this study observes the responses and language progress in a group of young children learning English through songs as a whole, to provide a comprehensive understanding. The results show that English songs significantly improve children's listening skills, vocabulary, and pronunciation. Through a fun and interactive approach, songs help children overcome emotional barriers in learning a new language, creating a supportive and less stressful learning environment. Additionally, the rhythm and repetition in songs facilitate the memorization and understanding of new words and phrases. The study also found that children are more motivated and show greater interest in learning English when using songs. Therefore, the application of English songs is recommended as an effective strategy for teachers and language instructors to support second language development in children. This study underscores the importance of innovation in language teaching methods and supports the use of musical media as an educational tool that positively impacts children's linguistic development.